Evolución del empleo en México: 1895-1980 - Rendón Gan, María Teresa; Salas, Carlos (El Colegio de México A.C., 1987)
This paper analyzes the changes both the level of employment and its structure (according to the different economic sectors) underwent between 1895 and 1980 in Mexico. The analysis is based on the employment figures which appear in different census; these figures have been homogenized by the authors. Not only does this paper point out the long-term tendencies of global and sectorial employment, but it also makes evident the existence of three distinct phases within the period mentioned above. The first phase (1895-1930) comprises the end of the apogee associated with the process of accumulation based on the exportation of metals and of certain agricultural products. It also includes a long period of economic stagnation which corresponds to the crisis which characterizes this stage of the country's development. The second phase (1930-1970) comprises the expansion period associated with an accumulation pattern centred around the section of the manufacturing sector which directs its interests towards the internal market. There are two stages in this phase: from 1930 to 1950 when there is a transition from one pattern to another, and from 1950 to 1970 when industrial development is finally consolidated. Finally, in the seventies, development has come up against serious problems which make further progress extremely difficult. In each of these three phases, employment acquires distinctive characteristics regards its rythm of growth and its structure according to spheres of employment. Throughout the text the authors point out the existence of some long-term tendencies present in the changes that have occurred both in the volume and in the composition of employment. They also pose a number of questions in relation to what caused some of the changes employment has undergone during the period analyzed.